Low cost network penetration device using Raspberry Pi / Adam Ibrahim - Ibrahim, Adam (2015)
Network penetration testing basically known as the proses of actively and systematically testing a deployed network in order to determine the security weakness of the network and what vulnerabilities may be present. Based on the penetration test report, the action can be taken to mitigate or resolve the vulnerabilities of the network. The portable penetration device are quiet costly and penetration tester commonly use a laptop with Kali Linux installed to performed the test in order to save cost without purchasing any portable penetration device. This paper presented how to setup the low cost penetration device by using Raspberry Pi and Kali Linux. By installing Kali Linux at the Raspberry Pi board, a simple penetration test is being conducted with virtual penetration lab that have been created by using GNS3 and verified that Raspberry pi with Kali Linux are suitable acting as penetration device. This experiment also shown the performance between Raspberry Pi and Laptop arc quiet similar in term of scanning time of Nmap tool when performing Discovery Scanning, Port Scanning, Fingerprinting and Vulnerability Scanning.